TECHNICAL CONDITIONS FOR HUMPING OF LONG WAGON IN MARSHALLING YARDS - Marton, Peter (Doprava a spoje, 2012)
There are hundreds of active marshalling yards in the Europe. Since marshalling yards are a necessary facility to perform single wagonload transportation efficiently for large traffic volumes, an important part of the infrastructure analysis in frame of the VEL-Wagon project was to assess the ability to pass over the hump in marshalling yards. The basic idea of the VEL-Wagon project was to develop design of versatile, efficient and longer wagon for European transportation. Reason for it was, that in the future, longer loading surfaces without interruptions, as well as more capable platforms with higher axle loads and with lower loading heights will be necessary in freight wagon design, to increase the capacity of the freight railway transportation. Conditions for freight wagons desing to pass over the hump are defined in TSI WAG. One condition defines that vehicles must be capable of passing over activated rail brakes and other shunting or stopping devices located on non-vertically curved track of convex transition curves of radius Rv = 250 m. This paper presents results of survey concerning this condition by relevant European railway infrastructure managers.